Approximate Derivations with the Radical Ranges of Noncommutative Banach Algebras - Jaiok Roh; Ick-Soon Chang (Abstract and Applied Analysis)
We consider the derivations on noncommutative Banach algebras, and we will first study the conditions for a derivation on noncommutative Banach algebra. Then, we examine the stability of functional inequalities with a derivation. Finally, we take the derivations with the radical ranges on noncommutative Banach algebras.